Antioxidant activity of polysaccharide from Garcinia mangostana rind and their derivatives - Zhenjie Tang; Gangliang Huang (BMC, 2024)
Abstract Background Polysaccharide from Garcinia mangostana rind has many biological activities and deserves further research. Methods The antioxidant properties of UAEE-GMRP, UAEE-GMRP-1 A, CM-30, and Ac-30 were evaluated through two different antioxidant activity experimental systems. Results The four polysaccharides had a better scavenging effect on hydroxyl radicals, while their inhibitory effect on lipid peroxidation was relatively weak. However, overall, the four polysaccharides showed a certain degree of potential application in the two antioxidant experiments mentioned above, especially the chemically modified polysaccharides from Garcinia mangostana rind, which effectively improved their antioxidant activity. This also indicates that chemical modification is a better method to improve polysaccharide activity. In addition, in these two antioxidant exploration experiments, carboxymethylated polysaccharide showed stronger activity compared to the other three polysaccharides. Conclusion The carboxymethylation modification may have great potential for application.